Users evaluation on the effectiveness of ES usage at Jabatan Akauntan Negara Malaysia (JANM), Putrajaya / Fazlina Mohd Ali - Mohd Ali, Fazlina (2012)
Several organizations report success and significant process gains resulting from enterprise system (ES) implementation. In order to enhance their business process the deployment of ES is emerging around the globe. Enterprise System is also referring to Enterprise Resource Planning (ERP), is large integrated system development to meet needs of internal departments in an organization (Strong & Volkoff, 2010). Therefore, to distinguish the actual state of a company after the ES implementation, it is crucial to do assessment or evaluation on their Enterprise System. This research chose Jabatan Akauntan Negara Malaysia (JANM), Putrajaya as the case study to conduct evaluation on their ERP system. JANM is one of government department under Ministry of Finance (MOF), who implemented ERP on year 2005. The official government ERP system launched by JANM is Government Financial Management and Accounting System (GFMAS), product by SAP. After the implementation of the system, no formal or informal evaluation was conducted. Hence, this project to evaluate the system from users' perspectives is crucial in determining value for cost to assist the organization in understanding the value of the investment in daily operations. The Enterprise System Success (ESS) Model by Sedera et al. (2004) is used throughout this study to ensure the effectiveness of Enterprise System is evaluated accurately. Survey is conducted to 140 users with 106 completed survey returned. Results of the survey were analyzed using Statistical Program for Social Science (SPSS) software, version 15. The statistical data are presented in tabular form as well as its graphical representation to enhance understanding of the results of the study. The survey result, pointed out that 78.3% from 106 users perceived that the ERP system in JANM is effective to support them in their daily tasks. These valuable findings contribute to the top management of Information Technology (IT) of the organization in order to get overview of current state of the employees' performance and ERP impact. Furthermore, the findings from this research are helpful to JANM in order for them to judge level of effectiveness of the application among employees.